Effect of bubble size on underwater noise spectra. (January 2015) - Mohanty, A.R.; Fatima, S.; Chandravanshi, M.L.
Highlights: Bubble size measurement by digital image. Procedure to create artificial rain drops. Measurement of bubble resonating frequency. Abstract: This paper describes the interpretations of underwater noise spectra of rainfall on water bodies. It uses a simple methodology of measurement of bubbles of various sizes up to 10 mm in diameter and the comparison of resonating frequencies of the above bubbles with theoretical calculations. The underwater noise of rainfall is a combined effect of drop impacts and bubble bursting. The rain drop size during actual rainfall varies between 0.8 and 5 mm in diameter and the underwater bubble sizes can vary from 0.5 mm to 10 mm in diameter. The detailed description of the experimental results of the underwater spectrum of natural light rain and artificially generated rain are presented. By analyzing the resonating frequencies of underwater bubbles for different type of rainfall, it is plausible to interpret the underwater noise spectrum of rainfall on water bodies and then predict the amount of rainfall.